Teachers' Best Practices in Teaching University Students - Oluyinka, Dr. Solomon; Endozo, Dr. Anatalia N. (IJRDO- Journal of Educational Research, 2019)
This study was therefore designed to analyze the best practices of 36 selected teachers teaching college physical education. the study used descriptive survey design. Systematic random sampling and purposive sampling were used to select the teacher-respondents. Data were collected and generated through the questionnaire, interview and observation techniques. Frequency tables, graphs and descriptive statistics were used to present quantitative data while qualitative data was presented as transcripts and in themes. The study established that the respondents’ ages are still at their young age of below thirty years old. There is an almost equal distribution of the number of male and female teacher respondents with 16 males and 20 females. Majority of the respondents had 5 to 10 years of teaching experience. Teacher respondents met the minimum requirements of a college instructor of having master’s degree. Majority of the respondents always observed the different best practices considering the area of class management and instruction. There is a high percentage or majority of the respondents are fully aware and always observed the best practices as far as the utilization of equipment and facility is concerned. There are almost 40% of the respondents who seldom follow the best practices as far as the technology used is concerned. The investigation suggests educators ought to persistently and dependably keep themselves side by side with the ongoing accepted procedures in teaching physical education. It is likewise imperative that physical educators will ceaselessly turn out to be progressively exploratory as far as how they will make the classroom condition increasingly favorable and pleasant to the student.